Integrating biorefinery and farm biogeochemical cycles offsets fossil energy and mitigates soil carbon losses. Issue 4 (1st June 2015) - Adler, Paul R.; Mitchell, James G.; Pourhashem, Ghasideh; Spatari, Sabrina; Del Grosso, Stephen J.; Parton, William J.
Abstract : Crop residues are potentially significant sources of feedstock for biofuel production in the United States. However, there are concerns with maintaining the environmental functions of these residues while also serving as a feedstock for biofuel production. Maintaining soil organic carbon (SOC) along with its functional benefits is considered a greater constraint than maintaining soil erosion losses to an acceptable level. We used the biogeochemical model DayCent to evaluate the effect of residue removal, corn stover, and wheat and barley straw in three diverse locations in the USA. We evaluated residue removal with and without N replacement, along with application of a high‐lignin fermentation byproduct (HLFB), the residue by‐product comprised of lignin and small quantities of nutrients from cellulosic ethanol production. SOC always decreased with residue harvest, but the decrease was greater in colder climates when expressed on a life cycle basis. The effect of residue harvest on soil N2 O emissions varied with N addition and climate. With N addition, N2 O emissions always increased, but the increase was greater in colder climates. Without N addition, N2 O emissions increased in Iowa, but decreased in Maryland and North Carolina with crop residue harvest. Although SOC was lower with residue harvest when HLFB was used for power production instead of being applied to land, the avoidance of fossil fuel emissions to the atmosphere by utilizing the cellulose and hemicellulose fractions of crop residue to produce ethanol (offsets) reduced the overall greenhouse gas (GHG) emissions because most of this residue carbon would normally be lost during microbial respiration. Losses of SOC and reduced N mineralization could both be mitigated with the application of HLFB to the land. Therefore, by returning the high‐lignin fraction of crop residue to the land after production of ethanol at the biorefinery, soil carbon levels could be maintained along with the functional benefit of increased mineralized N, and more GHG emissions could be offset compared to leaving the crop residues on the land.